Neuroscience of nicotine : mechanisms and treatment - Preedy, Victor R. (Academic Press, 2019)
PointsReferences; Chapter 2: Maternal Smoking and Fetal Brain Outcome: Mechanisms and Possible Solutions; 2.1. Introduction; 2.2. Maternal Smoking and Brain Development; 2.3. Maternal Smoking and Neurocognitive Outcome; 2.4. Maternal Smoking and HI Encephalopathy; 2.5. Potential Mechanisms; 2.5.1. Brain Inflammatory Response; 2.5.2. Brain Oxidative Stress; 2.5.2.1. ROS; 2.5.2.2. Antioxidant Defense System; 2.5.3. Mitochondrial Function and Integrity; 2.5.3.1. Mitochondrial Membrane Functional Units; 2.5.3.2. Mitochondrial Integrity; 2.5.3.2.1. Fission Machinery.